CONSTRASTIVE LINGUISTICS AND TEXT LINGUISTICS - Sulaymonov Samariddin; Abdurakhmanova Zilola (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Annotation: Contrastive linguistics compares and contrasts different languages, text linguistics focuses on the analysis of texts within a single language or language variety. Contrastive linguistics aims to identify the differences between languages, while text linguistics aims to understand how texts function and convey meaning within a particular language or discourse community.